Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Perusahaan Yang Terdaftar di Bursa Efek Indonesia Periode 2023-2024 - Vijaya, Diota Prameswari; Rizky, Nina (Universitas Pendidikan Ganesha, 2025)
This study examines the determinants of financial performance of companies listed on the Indonesia Stock Exchange (IDX) during 2023-2024. Using panel data from 150 companies across various sectors, this research analyzes the impact of capital structure, firm size, liquidity, asset utilization, and corporate governance on financial performance measured by Return on Assets (ROA) and Return on Equity (ROE). The Fixed Effect Model reveals that leverage negatively affects financial performance, while firm size, current ratio, asset turnover, and board independence demonstrate positive significant relationships. The findings contribute to corporate finance literature in emerging markets and provide practical implications for management in optimizing financial performance